Helping in the context of refugee immigration. (April 2022) - Echterhoff, Gerald; Becker, Julia C.; Knausenberger, Judith; Hellmann, Jens H.
Abstract: We review psychological approaches of helping behavior in the context of refugee immigration. Refugee migration, compared with nonrefugee migration, is characterized by greater forcedness and related perils. Taking into account perceptions of forcedness and perils, we examine potential helpers' responses at each of four successive stages toward helping people in perilous, distressing, or emergency situations: (1) noticing and recognizing distressing, help-demanding conditions; (2) taking responsibility; (3) knowing how to help; and (4) transfer of one's knowledge into action. In so doing, we discuss the role of different motives and functions of providing help (e.g. preserving refugees' dependency or facilitating their autonomy) and implications of unequal power relations between help providers and refugees. Highlights: We focus on psychological approaches of help for refugees. Based on the PARI (Psychological Antecedents of Refugee Integration) model, we highlight the role of migration forcedness and perils. We consider the four-stage model and different motives of helping. We discuss factors and consequences of autonomy versus dependency-oriented help. Helping is placed in the context of intergroup power relations.